210Po and 210Pb concentration in zooplankton of the Syrian coastal waters (eastern Mediterranean Sea) - AL-MASRI, MOHAMMAD SAID; MAMISH, SAMER; ABDEL-HALEEM, MOHAMMAD; HANI DURGHAM, HANI (Mediterranean Marine Science, 2019)
210Po and 210Pb activity concentrations and their concentration ratio (CR) in marine zooplankton collected for the first time from the Syrian coastal waters (the eastern Mediterranean Sea) have been determined. The average activity concentrations of 210Po and 210Pb were 243±36 and 26.4±4.3 Bqkg-1 dw. The 210Po/210Pb activity ratio was found to be more than one in all zooplankton samples with an average of 9.2 (8.4 to 10), which indicates that the accumulation of 210Po in zooplankton does not come from the decay of the 210Pb only, and reflects a preferential bioaccumulation of 210Po over 210Pb. In addition, the Concentration Ratio (CR) for 210Po and 210Pb reached 104 and 103, respectively. This study will contribute to the radioecological reference database for zooplankton in the Mediterranean Sea.